Souvenir of the 1890 Trades Union Congress held in Liverpool (1890)
1890 1880-1914 "Souvenir of the 1890 Trades Union Congress held in Liverpool" [T0273.jpg], 1890 Joseph Goodman was the Secretary of the Congress and he collated newspaper cuttings, Congress documents, leaflets from fringe meetings, souvenirs of social events and other ephemera into this scrapbook.